Synthesis and structural control of multidimensional metal nitride nanostructures - Li, Yun (Nanyang Technological University, 2023)
Nanostructured metal nitrides are widely used in applications due to their attractive properties such as large surface area, high electrical conductivity, thermal stability and corrosion resistivity. However, conventional synthesis approaches typically require multiple processing steps and long heating treatments at high temperatures under hazardous ammonia environment. This thesis aims to develop direct one-pot synthesis strategies coupling transient laser heating with wet solution processing chemistry to form multidimensional metal nitrides of various morphologies, crystal phases, and physiochemical properties to broaden the functional property and application space.